The INCREASING COMPETENCY IN BASIC ENGINEERING OF HOUSEHOLD ELECTRICITY INSTALLATION FOR MADRASAH ALIYAH EMEYODERE STUDENTS-SORONG CITY: Peningkatan Kompetensi Dasar Teknik Dasar Instalasi Listrik Rumah Tangga Bagi Pelajar Madrasah Aliyah Emeyodere-Kota Sorong - Andreas Pujianto; Egbert Joshua Sirait; Boby Wisely Ziliwu; Bagas Prakoso; Arhandy Arfah; Jalila Syarief (Politeknik Kelautan dan Perikanan Sorong, 2022)
Society in general uses electrical energy as a source of energy needs. Household electricity is widely used for daily necessities such as cooking, moving water, washing clothes, ironing clothes, etc. The purpose of the training carried out for Madrasah Aliyah Emeyodere Sorong City students is expected to increase knowledge and skills in the installation of household electrical installations. The method used in training is the provision of theoretical material in lectures and discussions. The practical method is also used by installing household electricity with a PLN source, one socket, and controlling lights with a switch. Evaluation of training activities used pre and post-tests. The results of the t-test analysis conducted showed that the results of the post-test were significantly different from the pre-test with an average difference of 18.42. These results indicate an increase in the evaluation carried out.